O alinhamento entre o plano de governo e o PPA: o caso do município de Nilópolis - Amorim Filho, Mario Gomes de (2014)
The objective of this work is to identify the factors that influenced the attempt to transpose the campaign promises of major election for mayor of Nilópolis in the 2012 election for the PPA 2014 / 2017 . For this, the concepts of federalism , public management and planning tools were discussed in the theoretical framework. Interviews with technical and executive manager , the chairmen of the constitution and justice and the finance committee were held , as well as president of the city council of Nilópolis. It was found that the factors identified are responsible for the difficulty in promoting alignment between campaign promises and agreed in the PPA . The dependence of inter -governmental transfers and the scarcity of resources were the main factors that hindered implementation in the municipality of Nilópolis.